Cisplatin in 5% Ethanol Eradicates Cisplatin-Resistant Lung Tumor by Killing Lung Cancer Side Population (SP) Cells and Non-SP Cells - Niu, Qi (Frontiers Media S.A., 2013)
Cancer side population (SP) cells with cancer stem cell-like properties are thought to be responsible for lung cancer chemotherapy resistance and currently no drug can efficiently target them. Breast cancer resistance protein (BRCP/ABCG2) is a major drug transporter in protecting lung cancer SP cells from cytotoxic agents. We showed that a low concentration of ethanol, which inhibits many membrane proteins, inhibits ABCG2 in lung cancer SP cells. Furthermore, cytotoxic cisplatin (DDP) in 5% (vol/vol) ethanol kills SP plus non-SP cancer cells better than either treatment alone in eradicating chemoresistant lung tumors. We found that 5% ethanol did not reduce ABCG2 protein levels, but significantly reduced ABCG2 protein function by a Hoechst 33342 extrusion assay, an ATPase activity assay, and transmission electron microscopy. Further, DDP in 5% ethanol (5% ethanol–DDP) induced apoptosis of the SP plus non-SP cancer cells both in vitro and in vivo. In DDP-resistant A549/DDP lung tumor-bearing Balb/C nude mice, intratumoral injection of 5% ethanol–DDP regressed tumors and significantly improved survivals compared with 5% ethanol, DDP alone, or control. Intratumoral injection of 5% ethanol–DDP helped eradicate tumors in 30% (3/10) of the mice after 4 weeks treatment. By killing SP and non-SP cancer cells, 5% ethanol–DDP could eradicate DDP-resistant lung tumor and extend survival, providing a novel way to improve chemoresistant lung cancer survival for clinic.